Numerical simulation and prediction of spatial wind field under complex terrain. Issue 180 (September 2018) - Ren, Hehe; Laima, Shujin; Chen, Wen-Li; Zhang, Bo; Guo, Anxin; Li, Hui
Abstract: A computational fluid dynamics numerical simulation of a spatial wind field under a complex terrain was conducted, and a prediction model of wind characteristics was proposed based on the correlation of simulation results. A large eddy simulation turbulent model was employed to simulate the behavior of the turbulent flow of the spatial wind field by using OpenFOAM 4.0. Then, the prediction model of the spatial wind field was established according to the "triangle edge angle relationship" for the mean wind velocity and spatial correlation analysis for the fluctuating wind velocity. The predicted model was further validated by simulation velocity time histories, reaching good agreement with the simulated results, which indicated that the predicted model had a higher precision. Finally, the proposed model was utilized to predict natural wind field characteristics, and they were compared with field measurement data acquired from ultrasonic anemometers. A comparison of the fluctuating wind velocity time histories, mean wind speeds, and fluctuating wind velocity spectra indicated that the predicted model was practical.